Testing the effects of procedural justice and overaccommodation in traffic stops: a randomized experiment - Lowrey, Belén V. (Criminal justice and behavior, 2016)
Research shows that perceptions of procedural justice influence people?s trust, confidence, and obligation to obey law and legal authorities as well as their willingness to cooperate with and support legal authorities. Interpersonal interaction styles that are central to procedural justice theory also play a key role in communication accommodation theory (CAT). Based on video clips depicting a police traffic stop, we use a randomized experiment to test the effects of procedural justice and overaccommodation on trust in police, willingness to cooperate with police, and obligation to obey police and the law. The results demonstrate that procedural justice has more powerful effects than overaccommodation on reported trust and confidence in the officer, as well as respondents? obligation to obey and willingness to cooperate with the officer. Moreover, although procedural justice generated strong effects on encounter-specific attitudes, it did not exert any effect on more general attitudes toward police.